The effects of focused ultrasound pulsation of nucleus accumbens in opioid-dependent rats. Issue 4 (2nd October 2019) - Deveci, Erdem; Kılıç, Alperen; Yılmaz, Onur; Nabi, Aynur; Ergün, Arif Sanlı; Bozkurt, Ayhan; Kurtulmuş, Ayşe; Öztürk, Ahmet; Eşrefoğlu, Mukaddes; Aydın, Mehmet Şerif; Şahan, Ebru; Kırpınar, İsmet
ABSTRACT: Background: Deep Brain Stimulation (DBS) is the only modality proven to be effective on selective stimulation of the deep brain structures. It was previously reported that, by using DBS, stimulation of nucleus accumbens (NA), a region that plays a pivotal role in the pathogenesis of substance addiction, is effective for the treatment of substance addiction. Objective: The purpose of the current study was to observe how the morphine-conditioned place preference changed in rats by stimulating NA with a non-invasive method, focused ultrasound (US) and to detect whether there would be any tissue damage caused by US waves. Methods: We used low-intensity focused ultrasound (LIFU), a noninvasive modality, in a place conditioning model to stimulate NA in rats. Results: At the initial stage of our study, we used morphine to induce place preference. As expected, morphine administration caused significant place preference. After the place preference was obtained by morphine, we divided the rats into two groups. One group received LIFU waves to NA and the other group received only sham, that is, no stimulation with US waves. Rats in both groups were continued to receive morphine. Then, we investigated whether LIFU and sham will reduce morphine-induced place preference or not. We observed that morphine-induced place preference had an ongoing raise in the sham group while no raise was detected in the ultrasound group. Although LIFU prevented the rats from the raise, it did not cause a significant reduction of morphine preference. Conclusion: We state that there is a need for future studies to investigate the effects of low-intensity focused ultrasound as an alternative treatment modality in addiction.